PENCARIAN TOKO OBAT HERBAL HNI TERDEKAT MENGGUNAKAN FORMULA HAVERSINE - Ade Prayoga; Diana Ikasari; Widiastuti, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Technolog y developments have a positive impact on various aspects, including access to information, communication, and business transactions. Knowing information about the location of the object being searched for, such as the HNI drug store in this study, is very important when needed or in an emergency. One way to access location information is using an application on a smartphone. This research builds a mobile application to find the location of the nearest HNI drug store using the haversine formula. The Haversine formula is used to calculate the straight-line distance between coordinates based on latitude and longitude so that you can find the shop closest to the user's location. Mapping of drug shop locations based on coordinates was carried out in making this application, displaying the location of the nearest shop as well as complete information regarding the list of HNI herbal medicine shops. Testing of the application was carried out using the Black Box method and the distance calculation accuracy test using Haversine obtained a value of 99.97%, explaining that the Haversine Formula provides accurate distance estimates for the nearest shop recommendations